Bio-Organic Fertilizer: A Green Technology to Reduce Synthetic N and P Fertilizer for Rice Production - Naher, Umme Aminun; Biswas, Jatish Chandra; Maniruzzaman, Md.; Khan, Faruk Hossain; Sarkar, Md. Imran Ullah; Jahan, Afsana; Hera, Md. Hasibur Rahaman; Hossain, Md. Belal; Islam, Aminul; Islam, Md. Rafiqul; Kabir, Md. Shahjahan (Frontiers in Plant Science, 2021)
Decomposed organic materials, in combination with plant growth promoting bacteria (PGPB), are environmentally friendly and reduce synthetic fertilizer use in rice production. A bio-organic fertilizer (BoF) was prepared using kitchen waste (79%), chita dhan (unfilled rice grain) biochar (15%), rock phosphate (RP) 5% and a consortium of 10 PGPB (1%) to supplement 30% nitrogen and to replace triple super phosphate (TSP) fertilizer in rice production with improvement of soil health. PGPB were local isolates and identified using 16S rRNA partial gene sequences as Bacillus mycoides, Proteus sp, Bacillus cereus, Bacillus subtilis, Bacillus pumilus, Paenibacillus polymyxa, and Paenibacillus spp. Isolates were able to fix N2 by 0.07 to 0.14%, solubilize 0.01 to 0.12% phosphate and produce 0.01 to 4.0% indoleacetic acid. The performance of BoF was evaluated by16 field experiments and 18 farmers’ field demonstration trials during the year 2017 to 2020 in different parts of Bangladesh. Performances of BoF were evaluated based on control (T1), full synthetic fertilizer dose (FSFD) of N, P and K (T2), BoF (2 t ha-1) + 70% N as urea + 100% K as muriate of potash (MoP) (T3), 70% N as urea + 100% P as TSP + 100% K as MoP (T4) and 2 t ha-1 BoF (T5) treatments. At research station, average grain yield improved by 10 to 13% in T3 compared to T2 treatment. Depending on season, higher AEN (19 to 30%), PEN (8 to 18%), PFPN (114 to 150%), REN (3 to 31%) and HIN (14 to 24%), and AEP (22 to 25%), PFPP (9 to12%), AREP (15 to 23%), and HIP (3 to 6%) were obtained in T3 compared to T2 treatment. Research results were reflected in farmers’ field and significant (P< 0.05) higher plant height, tiller, panicle, grain yield, PFPN and PFPP were obtained in the same treatment. Application of BoF improved soil organic carbon by 6 to 13% along with increased number of PGPB as compared to FSFD. In conclusion, tested BoF can be considered as a green technology to reduce 30% synthetic N and 100% TSP requirements in rice production with improved soil heath.